Association between inflammation and neural plasticity biomarkers in olfactory neuroepithelium – derived cells and cognitive performance in patients with major depressive disorder - A. Toll; M. Portella; P. Robledo; M. Barrera-Conde; R. De La Torre; J.M. Ginés; C. Diez-Aja; V. Soria; P. Lopez-Garcia; V. Pérez-Solà; P. Alvarez (European Psychiatry, 2022)
Introduction Inflammation and neural plasticity play a significant role in major depressive disorder (MDD) pathogenesis and cognitive dysfunction. The olfactory neuroepithelium (ON), closely related to the central nervous system (CNS), allows a non-invasive, low-cost study of neuropsychiatric disorders. However, few studies have used ON cells to ascertain them as biomarkers for MDD.